An Open Mapping Theorem using Lower Semicontinuous Functions - RODRIGUES, Brian (Institutional Knowledge at Singapore Management University, 1989)
We give a simple and direct proof, using lower semicontinuous functions, of a generalization of the open mapping theorem for metrizable topological vector spaces (that are not necessarily locally convex) and operators with complete graph. Our result is in a form more applicable to applied (convex) analysis.